Development Of Silicon And Silicon Carbide Nanostructures For Photonic Applications - Naderi, Nima (2013)
In this study, the structural, optical, and electrical properties of silicon and silicon carbide nanostructures are developed for photonic applications. Visible and ultraviolet (UV) photodetectors are fabricated based on optimized porous silicon (PS) and porous silicon carbide (PSC) nanostructures. In the first category of this work, the high-porosity and uniform PS samples are generated using an innovative combination of electroless and pulsed photoelectrochemical etching techniques. The electroless chemical etching is optimized by applying the delay time of 2 min prior to the electrochemical process to obtain the highest porosity (83%) and uniformity and hence enhanced photoluminescence (PL) intensity. Next, thermal carbonization of freshly-prepared PS samples is carried out to stabilize their optical and electrical characteristics. In the second category, the high-porosity and uniform PSC samples are synthesized through optimization of etching current density. The optimized sample (with J = 20 mA/cm2) shows the highest porosity (76%), highest surface roughness (137 nm), the most intense PL peak, and the highest stability compare to the other PSC samples. In the third category, high-porosity and uniform porous-shaped SiC thin films are grown based on TC-PS substrates using RF magnetron sputtering. The post annealing process at 1200 °C improves uniformity, grain size (1380 nm), surface roughness (610 nm), PL intensity (237.3 a.u.) and Raman red-shift (24 cm–1). Photodetectors are subsequently fabricated by depositing Schottky contacts onto all porous samples. The results show that the optimized nanostructures of silicon and silicon carbide with high porosity and uniformity are suitable materials for visible and UV photodetection.